2020
DOI: 10.1080/14693062.2020.1792822
|View full text |Cite
|
Sign up to set email alerts
|

Who do you trust? How trust in partial and impartial government institutions influences climate policy attitudes

Abstract: While previous research shows that environmental policy attitudes depend on trust in government, existing studies have either focused exclusively on trust in politicians and democratic institutions (political trust) or conflated such measures with trust in a wider range of impartial government institutions and actors. In this study, we distinguish between trust in partial institutions that enact laws and policies on the one hand, and trust in impartial institutions that exercise government authority and enforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
2
36
1
4
Order By: Relevance
“…Our results complement a recent literature demonstrating that environmental policy preferences are influenced by trust in institutions, authorities, and other citizens, such as family, friends, and neighbors (Hammar and Jagers, 2006;Konisky et al, 2008;Jagers et al, 2010;Fairbrother, 2016;Kulin and Johansson Sevä, 2020). Specifically, trust is correlated with citizens' willingness to support taxes to curb pollution and climate change (Hammar and Jagers, 2006;Harring, 2013;Harring and Jagers, 2013;Birol and Das, 2012;Fairbrother, 2016;Xu and Li, 2016;Kulin and Johansson Sevä, 2020) and trust plays a role in determining the set of policies that individuals are willing to support (Zannakis et al, 2015;Lafuente et al, 2018;Harring, 2018). Similarly, government quality plays an important role in determining individuals' willingness to pay environmental taxes (Davidovic et al, 2020).…”
Section: Introductionsupporting
confidence: 87%
“…Our results complement a recent literature demonstrating that environmental policy preferences are influenced by trust in institutions, authorities, and other citizens, such as family, friends, and neighbors (Hammar and Jagers, 2006;Konisky et al, 2008;Jagers et al, 2010;Fairbrother, 2016;Kulin and Johansson Sevä, 2020). Specifically, trust is correlated with citizens' willingness to support taxes to curb pollution and climate change (Hammar and Jagers, 2006;Harring, 2013;Harring and Jagers, 2013;Birol and Das, 2012;Fairbrother, 2016;Xu and Li, 2016;Kulin and Johansson Sevä, 2020) and trust plays a role in determining the set of policies that individuals are willing to support (Zannakis et al, 2015;Lafuente et al, 2018;Harring, 2018). Similarly, government quality plays an important role in determining individuals' willingness to pay environmental taxes (Davidovic et al, 2020).…”
Section: Introductionsupporting
confidence: 87%
“…Previous studies have shown that support for specific climate and environmental policies, especially pollution taxes, reflects political trust (Klenert et al, 2018;Fairbrother et al, 2019;Davidovic and Harring, 2020;Kulin and Johansson Sevä, 2020). Most studies are based on observational data, but Fairbrother (2019) used a survey experiment to provide stronger evidence of a causal relationship.…”
Section: Climate Change Mitigationmentioning
confidence: 99%
“…It is not unimaginable that people with lower trust in the government would actually avoid public media channels and rather prefer commercial media because of their actual independence ( 32 ). This could then explain why commercial media audiences would be less in favor of the government's decisions, given the known link between trust in the government and support for policy [e.g., ( 33 )]. Future studies should explore this strand more concretely.…”
Section: Discussionmentioning
confidence: 99%